A review of biomechanical and psychosocial risk factors among workers - Muhammad Ruzairi, Khairulhafiy; Sukadarin, Ezrin Hani; Widia, Mirta; Alaman, A. (2023)
From the negative biomechanical experiences and psychosocial risk factors may contribute to Musculoskeletal Disorder (MSD) and it has been scientifically shown. In the last few years, there have been many systematic literature reviews on the correlation between risk factors and MSD, as well as several newly published papers but not for exact states combining risk factors. The current work aims to update the knowledge base on combining risk factors associated with MSD specifically. This review is conducted using the terms ergonomics, MSD, biomechanical, and psychosocial risk factors. The databases visited were Scopus, Google Scholar, Springer, CORE, ResearchGate, Elsevier, ScienceDirect, Semantic Scholar, and NIOSH Abstract. Based on the 52 literatures reviewed, White Finger Disorder (38.4%), general MSD (36%), and Lower Back Pain (23%), are the most dominant complaints among workers in various industries. The findings revealed that the biomechanical and psychosocial risk factors have a potential relationship when both can increase the susceptibility to MSD